2014
DOI: 10.1016/j.drudis.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive peptides and their therapeutic applications

Abstract: HighlightsT cell signaling has a pivotal role in autoimmunity and immunosuppression.Immunosuppressive pharmaceuticals often exhibit severe side-effects in patients.Gene-encoded peptides have potential as immunosuppressive drug candidates.Cyclotides are stable peptides that offer enhanced oral administration properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 89 publications
1
79
0
Order By: Relevance
“…Incidentally, cyclosporine A produced by the fungus Tolypocladium inflatum is also a cyclic (undeca)peptide and it is considered the prototype of a new generation of immunosuppressive drugs (42). Historically, cyclosporine A was instrumental to the development of modern immunopharmacology and it is still in clinical use today (29,36). Despite the limitations of such comparisons, we believe that the rich diversity of cyclotides (17,43) justifies their position as a treasure trove for drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentally, cyclosporine A produced by the fungus Tolypocladium inflatum is also a cyclic (undeca)peptide and it is considered the prototype of a new generation of immunosuppressive drugs (42). Historically, cyclosporine A was instrumental to the development of modern immunopharmacology and it is still in clinical use today (29,36). Despite the limitations of such comparisons, we believe that the rich diversity of cyclotides (17,43) justifies their position as a treasure trove for drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…In a head-to-head comparison of [T20K]kB1 and fingolimod, a recently approved orally bioavailable drug to prevent MS progression, the cyclotide seemed to be an advantageous therapeutic option when administered at a single dose; fingolimod was only effective with multiple administrations, and best at daily administration of its therapeutic dose. Consequently, cyclotides exhibiting oral activity are very promising acquisitions in drug discovery, not only regarding the treatment of MS but as a potential option for oral treatment of other autoimmune-related diseases (25,36). Successful advances in chemical and recombinant synthesis (37,38) as well as enzymatic folding (39) and cyclization (40) may yield affordable production of cyclotides at clinical scale in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…[86] The potential of grafted cyclotides in the context of multiple sclerosis has been also explored by grafting peptide sequences from the MOG35-55 epitope onto the cyclotide kalata B1. [87] …”
Section: Engineered Cyclotides With Novel Biological Activiesmentioning
confidence: 99%
“…We demonstrated that cyclotides, in particular T20K, inhibit T-cell proliferation by downregulation of IL-2 release as well as IL-2R/CD25 surface expression and effector activity performance (Gründemann et al 2013;Thell et al 2014). The cytokine IL-2 physiologically plays an important role in T-lymphocyte activation and acts as autocrine factor to stimulate T-cell proliferation (Malek and Bayer 2004).…”
Section: Cyclotides and Their Immunomodulatory Propertiesmentioning
confidence: 99%